Características estruturais, produtivas e bromatológicas dos capins tifton 85 e jiggs fertilizados com alguns macronutrientes - De Rezende, Adauton Vilela; Rabêlo, Flávio Henrique Silveira; Rabelo, Carlos Henrique Silveira [UNESP]; Lima, Poliana Patrícia; De Ávila Barbosa, Larissa; De Carvalho Abud, Marcella; Souza, Flávia Romam Costa (Universidade Estadual de Londrina, 2015)
The aim this study was to evaluate the effect of fertilization of Tifton 85 and Jiggs grasses with some macronutrients on the structural, productive and bromatologic characteristics. Were evaluated two grasses (Cynodon dactylon cv. Tifton 85 and C. dactylon cv. Jiggs) and five sources of fertilizer (three formulations NPK: 08-28-16, 30-00-20 and 20-10-10, and two sources nitrogen: urea and super N) in a factorial scheme 2 x 5, distributed in a completely randomized design with four replications. The planting of grasses without fertilization was performed to simulate a pasture located in low natural fertility. The highest yields (P = 0.009) and ratios of leaves (P < 0.001) were observed in Tifton 85 grass, resulting in a lower proportion of stems when compared to Jiggs grass. The sources of fertilizers used changed the weight and the proportion of leaves and stems, as well as the leaf/stem ratio, number of tillers and mass production of Tifton 85 and Jiggs grasses. There was a significative interaction between the study factors (grass and fertilizer) for concentrations of DM (P = 0.024), ADF (P = 0.012), hemicellulose (P = 0.007), DMD (P = 0.012), TDN (P = 0.012), DE (p = 0.012) and ME (P = 0.012) leaves and the protein content (p = 0.016) of the stem. In general, the application of 30-00-20 fertilizer resulted in lower ADF content in the leaves of Tifton 85 grass and higher DM, with higher energy content also, and providing super N implied lower ADF content and higher DM digestibility of Jiggs grass leaves. In the whole plant, the Jiggs grass had higher NDF (P = 0.017) compared to Tifton 85 grass, however, the concentration of ADF that grass was lower (P < 0.001) than Tifton 85 grass, which resulted in higher DM (P < 0.001) and energy intake (P < 0.001). The application of super N decreased the ADF content (P = 0.026) of grasses, mainly from Jiggs, implying an increase in the digestibility of DM (P = 0.026) and energy content (P = 0.026). Although there are differences between the two grasses, productive and nutritional characteristics make these excellent forage options for the introduction in livestock systems. The supply of NPK 20-10-10 and 08-28-16 formulation is suitable for the cultivation of Tifton 85 and Jiggs grasses by increasing mass production and improve the nutritional quality of the forage.
Structural, productive and bromatologic characteristcs of tifton 85 and jiggs grasses fertilized with some macronutrients
Keywords: Cynodon dactylon; Morphology; Nitrogen; Nutritional value; Phosphorus